Clinical performance of a giomer-based pit and fissure sealant with and without air-abrasion pretreatment: a 12-month randomized clinical trial - Yomna Sayed Khallaf; Olfat Elsayed Hassanein; Aya Mohamed Adly; Dina Kamal (BMC Oral Health, 2026)
Abstract Background Pit and fissure sealants are widely used for caries prevention; however, their long-term success depends largely on retention. Giomer-based sealants containing surface pre-reacted glass ionomer fillers offer bioactive properties, yet concerns remain regarding their bonding durability when applied with mild self-etch primers. This randomized clinical trial evaluated the effect of bioactive glass air-abrasion pretreatment on the retention and caries preventive efficacy of a giomer-based sealant in young adults over 12 months. Methods This parallel-arm randomized clinical trial included 96 participants, each contributing one eligible sound permanent molar ( n = 48 per group). Participants were randomly allocated to either bioactive glass air-abrasion pretreatment followed by application of a giomer-based sealant (intervention group) or application of the same sealant without pretreatment (comparator group). Sealant retention and secondary caries incidence were evaluated at baseline, 6 months, and 12 months using Simonsen’s criteria, and modified United States Public Health Service (USPHS) criteria, respectively. The primary outcome was sealant retention at 12 months, whereas secondary caries incidence was assessed as a secondary outcome. Intergroup comparisons were analyzed using the Chi-square test. Intragroup comparisons were analyzed using Cochran’s Q test followed by multiple comparisons. Relative risk with 95% confidence intervals was calculated. Statistical significance was set at p ≤ 0.05. Results At 6 months, complete sealant retention was observed in 91.7% of teeth in the intervention group and 75.0% in the comparator group, with no statistically significant difference between groups ( p = 0.068). At 12 months, complete sealant retention was significantly higher in the intervention group (87.5%) than in the comparator group (33.3%) ( p < 0.0001). Teeth in the intervention group exhibited an 81.25% lower risk of sealant retention failure compared with the comparator group (RR = 0.1875; 95% CI: 0.0864–0.4069; p < 0.0001). No differences in secondary caries incidence were detected between groups during the 12-month follow-up period ( p = 1.0000). Conclusions Bioactive glass air-abrasion pretreatment significantly improved the retention of a giomer-based fissure sealant compared with sealant application without pretreatment. No differences in secondary caries incidence were detected between groups during the 12-month follow-up period. Incorporating mechanical surface conditioning prior to sealant placement may enhance sealant retention without compromising preventive efficacy. Trial Registration https://clinicaltrials.gov/ , (NCT06003452), 15-08-2023.